2013
DOI: 10.1167/iovs.12-11530
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Displacement of the Lamina Cribrosa in Glaucoma: In Vivo Interindividual and Intereye Comparisons

Abstract: The central and midperipheral LC is located more posteriorly in glaucomatous than in normal eyes, as well as in eyes with VF defects compared to fellow eyes with no VF defects. These results support the concept of posterior LC displacement in glaucoma and provide the basis for future in vivo human studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 35 publications
(73 reference statements)
8
104
0
Order By: Relevance
“…Their subsequent study found a more posterior location of central and mid-peripheral LC in glaucomatous than in healthy eyes. 20 The present data consistently exhibited, via SS-OCT scans, verticalhorizontal PLCD difference in healthy eyes. Further, the present study explored, for the first time using SS-OCT, the increased vertical-horizontal PLCD difference in POAG eyes compared with age-matched healthy eyes.…”
Section: Discussionsupporting
confidence: 82%
“…Their subsequent study found a more posterior location of central and mid-peripheral LC in glaucomatous than in healthy eyes. 20 The present data consistently exhibited, via SS-OCT scans, verticalhorizontal PLCD difference in healthy eyes. Further, the present study explored, for the first time using SS-OCT, the increased vertical-horizontal PLCD difference in POAG eyes compared with age-matched healthy eyes.…”
Section: Discussionsupporting
confidence: 82%
“…posterior sclera, may affect tissue responses in a way that would diminish pressure-related conformational changes in older patients with severe glaucoma. 15 LC is located more deeply in glaucomatous eyes 7 ; thus, postoperative edema of the ONH and the choroid could theoretically be an additional contributory factor to the early cupping reversal, as previously suggested by Greenidge et al 2 and Spaeth et al 29 In our cohort, IOP was successfully reduced to a presumably safe 30 level (11.5 -2.6 mmHg). Konstas et al 31 evaluated the 24-h IOP in patients with OAG treated with trabeculectomy versus maximal tolerated medical therapy and found that a successful trabeculectomy provides statistically lower mean, peak, and range of IOP for the 24-h period than maximal tolerated medical therapy in advanced glaucoma patients.…”
Section: Figsupporting
confidence: 76%
“…A straight reference line (RL) was drawn by one investigator (AR) masked to scan order between opposite edges of the opening in Bruch's membrane. 6,7,12,20 For study purposes, the cup area was defined as the cross-sectional optic disc area circumscribed by the RL (vitreal side) and the prelaminar tissue (toward the LC). Then, the uniformly dark area was automatically identified by Photoshop using the Color Selection tool with a tolerance of eight ( Fig.…”
Section: Image and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…6 The LC is located more posteriorly within the ONH in glaucomatous eyes than in healthy eyes, based on histologic studies using glaucomatous eyes or in vivo studies using enhanced depth imaging optical coherence tomography (EDI OCT). [7][8][9] Therefore, a deep LC may indicate that the ONH has been put under substantial mechanical stress.…”
mentioning
confidence: 99%